Efficacy and safety of ondansetron for morning sickness in pregnancy: a systematic review of clinical trials - Ashour, Ahmed M. (Frontiers in Pharmacology, 2023)
Background: Ondansetron is a selective antagonist of the serotonin 5-HT3 receptor that is commonly used to treat morning sickness. It is estimated that 70-80% of pregnant women suffer from morning sickness, a condition characterized by nausea and vomiting. However, it is still controversial regarding its safety during pregnancy, and continued research will be necessary to fully understand the risks and benefits associated with its use. Therefore, we aimed to identify and provide details of the efficacy and safety of ondansetron in clinical trials.A search was conducted of the ClinicalTrials.gov database on April 13th, 2023, using the search term "ondansetron and pregnancy." Inclusion and exclusion criteria were defined to identify relevant clinical trials. The inclusion criteria encompassed clinical trials related to pregnancy that utilized ondansetron as a treatment, while other clinical trials were excluded from consideration. All data extractions such as study title, study status, study type, intervention details, and outcome were collected.Results: A total of 18 clinical trials were identified, of which only 6 focused on studying the effects of ondansetron. Their respective study titles, statuses, conditions, interventions, outcome measures, and enrollment sizes have been tabulated in detail for easy reference. The information collected from these trials will contribute to our understanding of the potential benefits and risks of ondansetron in the context of pregnancy and its complications.Ondansetron has been shown to be an effective treatment for nausea and vomiting, including pregnancy-related morning sickness. Further research is needed to better understand the potential risks and benefits associated with its use in pregnant women.